2016
DOI: 10.1517/17425255.2016.1125881
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and challenges in using human hepatocytes in cytochromes P450 induction assays

Abstract: Primary cultures of HHs had long been considered as a gold standard for induction assays of xenobiotic-metabolizing enzymes. Owing to several shortcomings of HHs, alternative approaches such as immortalization of HHs, use of cell lines, generation of clonal cell lines from HHs, use of induced pluripotent stem (iPS) cells, cells from humanized animals, etc., were employed. While yielding particular advantage, overall, alternatives to HHs still remain an avenue for discrete applications or technical situations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Recently, human hepatocyte-like cells differentiated from human embryonic stem (ES) cells and induced-pluripotent stem (iPS) cells have gained much attention not only due to their promise for regenerative medicines, but also due to their potential for modeling drug metabolism and pathogen infection in vitro 1011121314. For example, human hepatocyte-like cells differentiated from these stem cells can be stably supplied thanks to the indefinite proliferation potential of ES and iPS cells.…”
mentioning
confidence: 99%
“…Recently, human hepatocyte-like cells differentiated from human embryonic stem (ES) cells and induced-pluripotent stem (iPS) cells have gained much attention not only due to their promise for regenerative medicines, but also due to their potential for modeling drug metabolism and pathogen infection in vitro 1011121314. For example, human hepatocyte-like cells differentiated from these stem cells can be stably supplied thanks to the indefinite proliferation potential of ES and iPS cells.…”
mentioning
confidence: 99%
“…First, we have shown that the EC matrix selectively promotes the expression levels of metabolizing enzymes including phase I metabolizing enzymes (CYP1A2, CYP2B6, CYP2C9, CYP2E1 and CYP3A4), a phase II metabolizing enzyme (NAT2) and transporters (ABCC2, SLC22A5 and DPP4) in hASC‐HLCs. These proteins have been extensively studied in hepatocytes because of their implication in drug metabolism and toxicologic processes in adult hepatocytes . More importantly, the activities of CYP2C9 and CYP3A4 in the hASC‐HLCs cultured on the EC matrix were found to be significantly increased compared to those in the cells cultured on the collagen I‐coated substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Human Hepatocytes. Unlike HLMs, human hepatocytes contain native receptors and drug metabolizing enzymes, as well as transporters, and remain the gold standard for assessing the induction of drug metabolizing enzymes, particularly the P450s, by NCEs and other xenobiotics (Fahmi and Ripp, 2010;Dvorak, 2016; https://www.fda. gov/regulatory-information/search-fda-guidance-documents/vitro-druginteraction-studies-cytochrome-p450-enzyme-and-transporter-mediateddrug-interactions).…”
Section: Traditional Chinese Medicinementioning
confidence: 99%